PREVALENSI SINDROMA METABOLIK PADA POPULASI PENDUDUK BALI, INDONESIA - Dwipayana, M Pande; Suastika, K; Saraswati, IMR; Gotera, W; Budhiarta, AAG; -, Sutanegara; Gunadi, IGN; Badjra Nadha, K; Wita, W; Rina, K; Santoso, A; Kajiwara, N; Taniguchi, H (journal of internal medicine, 2011)
An epidemiological study on metabolic syndrome (MS) in seven villages population of Bali (6 villages and 1 suburban),Indonesia have been conducted. One thousand eight hundred fourty (age, 13 " 100 year; M/F, 972/868) subjects were recruitedin the study. Criteria for obesity was based on WHO for Asia PaciÃž c population (2000) and for MS based on a joint statement ofIDF, NHLBI, AHA, WHF, and IAS (2009). The prevalence of central obesity based on waist circumference (WC) was 35% (M,27.5%; F, 43.4%) and MS was 18.2% (M, 16.6%; F, 20.0%).Waist circumference, as a central role in metabolic syndrome, hassigniÃž cant correlation with other components of metabolic syndrome, i.e. diastolic blood pressure (R = 0.129; p < 0.001), fastingblood glucose (R = 0.088; p < 0.001), HDL cholesterol (R = -0.066; p = 0.006), triglyceride (R = 0.349; p < 0.001), and totalcholesterol (R = 0.179; p < 0.001).Of the study could be concluded as follow: the prevalence of obesityand MS were relativelyhigh; Waist circumference was correlated with other components of metabolic syndrome and the best parameter for predictingmetabolic syndrome.